Technology offers solutions to the current power crisis. - Stahlkopf, K.
The rolling blackouts and soaring prices now besetting California's electric system are only the first and most visible signs of deeper problems affecting the US grid. Among them are neglect of the nation's electrical infrastructure, poorly structured electricity markets, and a lack of incentives for new investment. Ultimately, most of these problems spring from a lack of understanding of the power system's unique nature and technical complexity, resulting in a hodgepodge of policies that ignores both technological and economic reality. Fortunately, a variety of new technologies are available to help resolve these fundamental issues in a cost effective, expeditious manner. The most effective short-term step that can be taken to ease the California crisis and help prevent its spread is to improve load management. Electricity customers need to be given incentives to conserve energy when it would do the most good from a power market standpoint. Other technologies can be applied on the supply side in the medium-to-long term including fossil plant upgrades and application of FACTS devices
Keywords: California; FACTS devices; Electricity prices; Energy conservation incentives; Fossil plant upgrades; Load management; Power crisis; Power market standpoint; Rolling blackouts; Short-term step; Supply side technologies